Paleomagnetism of upper permian basaltic rocks of Cam Thuy formation from Thuan Chau locality, Son La, Northwest Vietnam - Chi, Cung Thuong; Geissman, John W.; Quy, Hoang Van; Anh, Tran Viet; Dung, Nguyen Thi Phuong (Vietnam Journal of Earth Sciences, 2015)
Oriented-core samples (74) from eight sites collected from the Late Permian basaltic Cam Thuy formation exposed at Thuan Chau locality, Son La Province, northwestern Vietnam yield interpretable magnetizations in progressive demagnetization. The characteristic remanent magnetization (ChRM) components carried by magnetite and hematite are successfully isolated from secondary components reveal a mean, stratigraphic coordinates paleomagnetic direction of Ds = 216.1o, Is = 10.5o (α95 = 8.9o, k = 107.8, N = 7 site mean directions), corresponding to a virtual geomagnetic pole located at λ = 45.6 oN, f = 226.8 oE and a paleo-latitude for the study area situated at ±5.3 oN during the Late Permian. A comparison of the pole we report in this study with the Late Permian pole of South China Block shows that this basaltic terrane of northwest Vietnam has been close to if not a coherent part of the South China Block since Late Permian. This result implies that insignificant cumulative displacement has occurred along the Ailao Shan/Red River fault system during the Cenozoic India-Eurasia collision.References Achache, J., and V. Courtillot, 1985: A preliminary Upper Triassic paleomagnetic pole for the Khorat Plateau (Thailand): Consequences for the accretion of Indochina against Eurasia. Earth Planet. Sci. Lett., 73, 147-157. Cai, J.-X., Zhang, K.J., 2009: A new model for the Indochina and South China collision during the Late Permian to the Middle Triassic. Tectonophysics 467, 35-43. Chan, L.S., Wang, C.Y., and Wu, X.Y., 1984: Paleomagnetic results from some Permian-Triassic rocks from southwestern China. Geophys. Res. Lett., 11, 11, 1157-1160. Chen, Y., and V. Courtillot, 1989: Widespread Cenozoic (?) remagnetization in Thailand and its implications for India-Asia collision. Earth Planet. Sci. Lett., 93, 113-122. Cung Thuong Chi, 1996: Paleomagnetism of Mesozoic and Cenozoic rocks from Vietnam: Implications for the Tertiary tectonic history of Indochina and a test of the extrusion model. Ph.D. Dissertation, 228pp., Texas A&M University, College Station, Texas, USA. Cung Thuong Chi, Nguyen Quoc Cuong, Nguyen Trong Yem, 2000a: Preliminary paleomagnetic results of Late Permian-Early Triassic basalts from northwestern Vietnam and their tectonic implications. Journal of Geology, A/259, 7-8/2000, 1-8 (In Vietnamese). Cung Thuong Chi, Nguyen Trong Yem, Nguyen Quoc Cuong, 2000b: Paleomagnetic study on Late Jurassic-Cretaceous extrusive and intrusive rocks from northwestern Vietnam. Journal of Geology, A/256, 1-2/2000, 1-8. (In Vietnamese). Dercourt, J., Ricou, L.E., Vrielynck, B. (Eds.), 1993: Atlas Tethys Palaeoenvironmental Maps Gauthier-Villars, Paris 307pp., 14 maps, 1 plate. Enkin, R.J., 1990: Formation et deformation de l’Asie depuis la fin de l’ere primaire: les apports de l’etude paleomagnetique des formations secondaires de Chine du Sud. Ph.D. Thesis, 333 pp., Univ. de Paris 7. Enkin, R.J., Yang, Z., Chen, Y., and Courtillot, V., 1992b: Paleomagnetic constraints on the geodynamic history of the major blocks of China from the Permian to the present. J. Geophys. Res., 97, B10, 13,953-13,989. Fang, W. and Van der Voo, R., 1990: Paleomagnetism of the Late Permian Emeishan basalt, Yunnan, China. Eos Trans. AGU, 71, 488. Fisher, R.A., 1953: Dispersion on a sphere. Proc. Roy. Soc. London, Series A, 217, 295-305. Gatinsky, Y.G., and C.S. Hutchinson, 1986: Cathaysia, Gondwanaland and the Palaeotethys in the evolution of continental Southeast Asia. Proceed. GeoSea V Congress, Geol. Soc. Malaysia Bull., 20. Glotov, A.I., Polyakov, G.V., Hoa, T.T., Balykin, P.A., Akimtsev, V.A., Krivenko, A.P., Tolstykh, N.D., Phuong, N.T., Thanh, H.H., Hung, T.Q., Petrova, T.E., 2001: The Ban Phuc Ni-Cu-PGE deposit related to the Phanerozoic komatiite-basalt association in the Song Da rift, northwestern Vietnam. Can. Mineral. 39, 573-589. Hanski, E., Walker, R.J., Huhma, H., Polyakov, G.V., Balykin, P.A., Tran, Trong Hoa, Ngo, Thi Phuong, 2004: Origin of the Permian-Triassic komatiites, northwestern Vietnam. Contributions to Mineralogy and Petrology 147, 453-469. Heller, F., Lowrie, W., li, H. and Wang, J., 1988: Magnetostratigraphy of the Permo-Triassic boundary section at Shangsi (Guanggyuan, Sichuan, China). Earth Planet. Sci. Lett., 88, 348-356. Huang, K., Opdyke, N., Kent, D., Xu, G., and Tang, R., 1986: Further paleomagnetic results from the Permian Emeishan basalts in SW China (in Chinese). Kexue Tongbao, 31, 1192-1201. Huang, K., Opdyke, N.D., Kent, D.V., Xu, Guizhong, Tang, Ruolong, 1986: New paleomagnetic results of Permian Emeishan basalts. Chinese Science Bulletin 2, 133-137 (in Chinese). Huang, K., Opdyke, N.D., 1998: Magnetostratigraphic investigations on an Emeishan basalt section in western Guizhou province, China. Earth and Planetary Science Letters 163, 1-14. Hutchinson, C.S., 1989: The palaeo-Tethyan realm and Indosinian orogenic system of Southeast Asia. In: Sengor, A.M.C. (Ed.). Tectonic Evolution of the Tethyan Region, 585-643, Academic San Diego, California, 1989b. Kirschvink, J.L., 1980: The least-square line and plane and the analysis of paleomagnetic data. Geophys. J. R. Astron. Soc. London, 62, 699-718. Lacassin, R., Leloup, P.H., Trinh, P.T., Tapponnier, P., 1998: Unconformity of red sandstones in north Vietnam: field evidence for Indosinian orogeny in northern Indochina? Terra Nova 10, 106-111. Lepvrier, C., H. Maluski, Vu Van Tich, A. Leyreloup, Phan Truong Thi, Nguyen Van Vuong, 2004: The Early Triassic Indosinian orogeny in Vietnam (Truong Son Belt and Kontum Massif); implications for the geodynamic evolution of Indochina. Tectonophysics 393, 87- 118. Lepvrier, C., Nguyen Van Vuong, Henri Maluski, Phan Truong Thi, Tich Van Vu, 2008: Indosinian tectonics in Vietnam. C. R. Geoscience 340, 94-111. Li, Z.X., Powell, C.McA., 2001: An outline of the palaeogeographic evolution of the Australian region since the beginning of the Neoproterozoic. Earth Science Reviews 53, 237-277. Li, Z.X., Zhang, I., Powell, C.McA., Trench, A., 1993: Palaeozoic global reconstructions, In: Long, J.A. (Ed.). Palaeozoic Vertebrate Biostratigraphy and Biogeography. Belhaven Press, London, pp. 25-53. Lin, J.L., 1984: The apparent polar wonder paths for the North and South China blocks. Ph.D. Thesis, 248 pp. Univ. of California, Santa Barbara. Liu, C., Zhu, R. and Jing, Z., 1985: Paleomagnetic study of Late Permian Emeishan basalts from Panxi and its neighbouring areas (in Chinese). In: Contributions to Panxi rift, China, Vol. 2, edited by Y. Zhang, pp. 194-200, Geological Publishing House, Beijing. Lung, S.C.,Wang, C.Y.,Wu, X.Y., 1984: Paleomagnetic results from some Permian-Triassic rocks from southwestern China. Geophysical Research Letters 11 (11), 1157-1160. McElhinny, M.W., 1981. Fragmentation of Asia in the Permian. Nature 293, 212-216. Metcalfe, I., 1988: Origin and assembly of Southeast Asia continental terranes, Gondwana and Tethys, In: Audley-Charles, M.G., Hallam, A. (Eds.). Geological Society of London Special Publication 37, 101-118. Metcalfe, I., 1991: Late Palaeozoic and Mesozoic palaeogeography of Southeast Asia. Palaeogeography, Palaeoclimatology, Palaeoecology 87, 211-221. Metcalfe, I., 1996: Pre-Cretaceous evolution of SE Asian terranes. In: Hall, R., Blundell, D. (Eds.). Tectonic Evolution of Southeast Asia. Geological Society of London Special Publication 106, 97-122. Metcalfe, I., 1998: Palaeozoic and Mesozoic geological evolution of the SE Asian region, multidisciplinary constraints and implications for biogeography. In: Hall, R., Holloway, J.D. (Eds.). Biogeography and Geological Evolution of SE Asia. Backhuys Publishers, Amsterdam, pp. 25-41. Metcalfe, I., 2002: Permian tectonic framework and palaeogeography of SE Asia. Journal of Asian Earth Sciences 20 (2002) 551- 566. Metcalfe, I., 2011: Tectonic framework and Phanerozoic evolution of Sundaland. Gondwana Research 19, 3-21. Metcalfe, I., 2012: Changhsingian (Late Permian) conodonts from Son La, northwest Vietnam and their stratigraphic and tectonic implications. Journal of Asian Earth Sciences 50 (2012) 141-149. Phan Cu Tien, 1977: Late Permian -Early Triassic sediments from northwestern Vietnam. In: The geological problems of NW Vietnam region, Science and Technique Publisher House, Hanoi, pp.109-151 (In Vietnamese). Polyakov, G.V., Tran Trong Hoa, Akimtsev, V.A., Balykin, P.A., Ngo Thi Phuong, Hoang Huu Thanh, Tran Quoc Hung, Bui An Nien, Tolstykh, N.D., Glotov, A.I., Petrova, T.E., Vu Van Van, 1999: Ore and geochemical specialization of Permo-Triassic ultramafic-mafic complexes in North Vietnam. Geologiya i Geofizika (Russian Geology and Geophysics) 40 (10), 1474-1487 (1453-1467). Sengor, A.M.C., 1979: Mid-Mesozoic closure of Permo-Triassic Tethys and its implications. Nature 279, 590-593. Sengor, A.M.C., 1984: The Cimmeride orogenic system and the tectonics of Eurasia. Geological Society of America Special Paper 195, 82. Sengor, A.M.C., 1987: Tectonic subdivisions and evolution of Asia. Bulletin of the Technical University of Istanbul 40, 355-435. Sengor, A.M.C., 1989: The Tethyside Orogenic System, an introduction, In: Sengor, A.M.C. (Ed.). Tectonic Evolution of the Tethyan Region. Kluwer, Dordrecht, pp. 1-22. Scotese, C.R., McKerrow, W.S., 1990: Revised world maps and introduction. In: McKerrow, W.S., Scotese, C.R. (Eds). Palaeozoic Palaeogeography and Biogeography. Geological Society Memoir 12, 1-21. Scotese, C.R., Golonka, J., 1992: Paleogeographic Atlas. Paleomap Progress Report 20-0692. Department  of Geology, University of Texas at Arlington, 34pp. Scotese, C.R., Langford, R.P., 1995: Pangea and the paleogeography of the Permian. In: Scholle, P.A., Peryt, T.M., Ulmer-Scholle, D.S. (Eds.). The Permian of northern Pangea. Paleogeography, Paleoclimate and Stratigraphy, Vol. 1, Springer, Berlin, pp. 3-19. Sone, M., Metcalfe, I., 2008: Parallel Tethyan Sutures in mainland SE Asia: new insights for Palaeo-Tethys closure. Compte Rendus Geoscience 340, 166-179. Steiner, M., Ogg, J., Zhang, Z. and Sun, S., 1989: The Late Permian – Early Triassic magnetic polarity time scale and plate motion of South China. J. Geophys Res., 94, 7343-7363. Takemoto, K., Halim, N., Otofuji, Y., Tran Van Tri, Le Van De, Hada, S., 2005: New paleomagnetic constraints on the extrusion of Indochina: Late Cretaceous results from the Song Da terrane, northern Vietnam. Earth. Planet. Sci. Lett., 229, 273-285. Tran Trong Hoa, 1996: Magmatic activities of Northwestern Truong Son belt in Mesozoic-Cenozoic. Material substances, forming conditions and mineral resource potential // J. Sci Earth. 18 (3), 218–227. Tran Trong Hoa, 2001: Division and Comparison of Permian-Triassic basaltoid complex of the Song Da zone. Journal of Geology A/265, 12-19, Hanoi, Vietnam (In Vietnamese). Van Der Voo, R., Fang, W., Wang, Z., Suk, D., Peacor, R., Liang, Q., 1993: Paleomagnetism and electron microscopy of the Emeishan basalts, Yunnan, China. Tectonophysics 221, 367-379. Yang, Z., Besse, J., 1993: Paleomagnetic study of Permian and Mesozoic sedimentary rocks from northern Thailand supports the extrusion model for Indochina. Earth Planet. Sci. Lett., 117, 525-552. Zhang, K.J., Cai, J.-X., 2009: NE-SW-trending Hepu–Hetai dextral shear zone in southern China: penetration of the Yunkai Promontory of South China into Indochina. Journal of Structural Geology 31, 737-748. Zhang, K.J., Cai, J.-X., Zhu, J.-X., 2006: North China and South China collision: insights from analogue modeling. Journal of Geodynamics 42, 38–51. Zhang, Z.K., 1984: Sino-Korea and Yangze blocks were a part of Paciﬁc paleocontinent in the Late Paleozoic. Bulletin of Chinese Academy of Geological Sciences 9, 45-54 (in Chinese). Zhao, X.X., Coe, R.S., 1987: Palaeomagnetic constraints on the collision and rotation of North and South China. Nature 327, 141-144. Zhou, M.F., Arndt, N.T., Malpas, J., Wang, C.Y., Kennedy, A.K., 2008. Two magma  series and associated ore deposit types in the Permian Emeishan large igneous province, SW China. Lithos 103, 352-368. Zhou, Y., Lu, L., and Zheng, B., 1986: Paleomagnetic polarity of the Permian Emeishan basalt in Sichuan (in Chinese). Geol. Rev., 32, 465-469. Zhou,Y.X., Lu, L.Z., Zhang, B.M., 1988: Preliminary paleomagnetic research for Panxi region. Collected Works for Panxi Rift No.3. Beijing Geological Publishing House, pp. 212-230 (in Chinese with English abstract). Zhuang, Z.H., Jiang, X.X., Pan, Z.X., 1989: Paleomagnetism of the formation and development of Central Sichuan palaeo-upwarp. A Research Report, pp. 1-87 (in Chinese). Ziegler, A.M., Hulver, M.L., Rowley, D.B., 1997: Permian World Topography and Climate, In: Martinin, I.P. (Ed.). Late Glacial and Postglacial Environmental Changes. Oxford University Press, New York, pp.111-146. Ziegler, A.M., Gibbs, M.T., Hulver, M.L., 1998: A mini-atlas of oceanic water masses in the Permian Period. Proceedings Royal Society of Victoria 110, 323-343. Zijderveld, J.D.A., 1967: A.C. demagnetization of rocks: Analysis of results, In: Methods in paleomagnetism, edited by D.W. Collinson, K.M. Creer, and S.K. Runcon, 254-286, Elsevier, New York. Zonenshain, L.P., Kuzmin, M.I., Kononov, M.V., 1985: Absolute reconstructions of the Palaeozoic oceans. Earth and Planetary Science Letters 74, 103-116.